The proportion of HIV disclosure to sexual partners among people diagnosed with HIV in China: A systematic review and meta-analysis - Peng, Wenwen; Song, Xiaohan; Zhang, Ci; Chen, Yuqing; Zhou, Qidi; Välimäki, Maritta Anneli; Li, Xianhong (Frontiers in Public Health, 2022)
Background: Sexual behavior is one of the main routes of HIV/AIDS spread. HIV disclosure to sexual partners has been confirmed to be an important strategy for HIV/AIDS prevention and control. We conducted a systematic review and meta-analysis to pool proportions and characteristics of HIV disclosure to sexual partners among people diagnosed with HIV in China. Methods: We searched 8 databases and extracted the data on HIV disclosure to partners. Heterogeneity of the data was tested with I². Published bias subjectively and objectively analyzed through the funnel plot and Egger's regression test. Subgroup analyses were performed to explore the variation in the proportion by sexual partnership types (unclassified, regular, casual sexual partners), whether being men who have sex with men (MSM), and when to diagnose. The sources of heterogeneity were analyzed. Sensitivity analysis was carried out to evaluate the stability of the results. Results: Out of 3698 hits, 44 studies were included in the review; 11 studies targeted on MSM. The pooled proportion of HIV disclosure to sexual partners was 65% (95% CI: 56, 75%). Sub-group analyses indicated the proportions of HIV disclosure to regular, casual and unclassified sexual partners were 63% (95% CI: 45, 81%), 20% (95% CI: 8, 33%), and 66% (95% CI: 59, 73%) respectively. Fifty-seven percent (95% CI: 45, 69%) disclosed on the day of diagnosis, 62% (95% CI: 42,82%) disclosed within one month, and 39% (95% CI: 2,77%) disclosed one month later. Among MSM, the disclosure to regular male partners, regular female sexual partners, spouses, and casual partner were 47% (95% CI: 29, 65%), 49% (95% CI: 33,65%), 48% (95% CI: 18, 78%) and 34% (95% CI: 19, 49%) respectively. Conclusions: The disclosure prevalence of people diagnosed with HIV to sexual partners was not high in China, and it varies among partner types, key populations, and time being diagnosed. HIV disclosure strategies and procedures need to be developed more detailed and tailored based on the pain points of disclosure status, so as to ultimately prevent HIV transmission through sexual contact. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022291631.